Sentidos no espaço urbano : os dizeres de Gentileza dentro e fora da cidade - Yado, Thaís Harumi Manfré (Universidade Federal de São Carlos, 2016)
This research has as theoretical scope the principles of Discourse Analysis (DA) French second array concepts postulates by Michel Pêcheux. We have the goal of building joints and analysis between the echoes the name of the Prophet Gentileza and his work – Urban book circulated by the space of the city of Rio de Janeiro. Through the discourses present in urban areas – social, symbolic, heterogeneous spaces, memory, full of meanings, movement of senses, spaces of enunciation. In the first chapter, we present how the businessman José Datrino becomes the Gentileza, after the burning of a circus in the city of Niterói. In the second chapter, we expose the traits that the subject position Prophet suffered over time, with your symbologies and influences. In the third chapter, we report about the Urban book, as the Prophet Gentileza turned a series of walls ashes in poetry in the open and that senses this artistic intervention can influence the life of the townspeople. In the fourth chapter, we show the deletion of the work of the Prophet that happened after his death, as the power of the State is imposing, but through the power of social movements that order-deletion given by the State is reviewed and the work is retrieved and protected as cultural heritage. And in the fifth and final chapter, we present echos the voice in Gentileza caused in society and that we can hear the echoes and references from their production, these echoes were shifted to other contexts and applied differently, but we can still see the features that refer us to the Prophet and his work, Urban book.
Keywords: Discurso; Memória; Espaço urbano; Profeta Gentileza; Livro Urbano; Discurse; Memory; Urban space; Prophet Gentileza; Urban Book; LINGUISTICA, LETRAS E ARTES